Epidemiological Characteristics of Poliomyelitis during the 21st century (2000-2013) - Tahir Ahmad; Sania Arif; Nazia Chaudry; Sadia Anjum (International Journal of Public Health Science (IJPHS), 2014)
Poliovirus is the pathogenic agent of paralytic poliomyelitis that belongs to the picornaviridae family. Poliomyelitis has an extended history dating over to the Egyptian eighteenth dynasty. It was recognized as distinct disease in the late nineteenth century when the world was ravaged by large number of outbreaks and epidemics in many countries. Paralytic Polio, the rarest but the most severe form of the disease, is characterized by acute flaccid paralysis of any or rarely both of the limbs. Increasing epidemics during the late 19th and 20th centuries lead to the initiation of a worldwide global effort for polio eradication in 1988, super headed by WHO and various other organizations. The launch of Global Polio Eradication Initiative together with the introduction of two polio vaccines resulted in 99% reduction of wild poliovirus cases worldwide while the total number of polio-endemic countries dropped from 24 countries in the year 2000 to only three countries in 2012; Afghanistan, Nigeria and Pakistan. This review will focus on the general biology of poliovirus, some historic and geographic epidemiological aspects of poliomyelitis eradication during the year 2000-2012 and also on the major failing factors associated with the efficiency of the vaccines to eradicate polio in Pakistan.